2017
DOI: 10.5194/acp-2017-859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol optical properties and trace gas emissions by PAX and OP-FTIR for laboratory-simulated western US wildfires during FIREX

Abstract: Abstract. Western wildfires have a major impact on air quality in the US. In the fall of 2016, 107 test fires were burned in the large-scale combustion facility at the US Forest Service Missoula Fire Sciences Laboratory as part of the Fire Influence on Regional and Global Environments Experiment (FIREX). Canopy, litter, duff, dead wood, and other fuel components were 15 burned in combinations that represented realistic fuel complexes for several important western US coniferous and chaparral ecosystems includin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(92 citation statements)
references
References 28 publications
9
80
3
Order By: Relevance
“…The time evolution of the MCE, and thereby information about the impact of flaming and smoldering on aerosol optical properties during stages of combustion, was lost due to the mixing of gases and aerosol in the combustion laboratory (Liu et al, 2013b;Pokhrel et al, 2016). The effect of MCE on aerosol optical properties is discussed in other FIREX studies (Liu et al, 2013b;Pokhrel et al, 2016;Selimovic et al, 2017).…”
Section: Comparison Of Integrated Scatteringmentioning
confidence: 99%
“…The time evolution of the MCE, and thereby information about the impact of flaming and smoldering on aerosol optical properties during stages of combustion, was lost due to the mixing of gases and aerosol in the combustion laboratory (Liu et al, 2013b;Pokhrel et al, 2016). The effect of MCE on aerosol optical properties is discussed in other FIREX studies (Liu et al, 2013b;Pokhrel et al, 2016;Selimovic et al, 2017).…”
Section: Comparison Of Integrated Scatteringmentioning
confidence: 99%
“…Emission ratios and emission factors (EFs) are based on fire-integrated excess values that benefit from significant signal averaging. Many of the above species have EFs that agree between PTR-ToF and FTIR within 10 % (Selimovic et al, 2017; Table S8). Additionally, it has been shown that the FTIR fire-integrated emission factors derived for hydroxyacetone are in excellent agreement with that reported for real wildfires by Liu et al (2017b;Selimovic et al, 2017).…”
Section: Comparison With Op-ftirmentioning
confidence: 99%
“…Several other types of fuels were also burned, but with fewer replicates, and these included additional pine species (loblolly and Jeffrey pine), bear grass, rice straw, Ceanothus, dung, peat, excelsior, and commercial lumber. Experiments with western fuels included the combustion of both specific components of the fuel, such as canopy, litter, and duff, and more realistic burns that included a mix of components (Selimovic et al, 2017).…”
Section: Fire Sciences Laboratory Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations